MODELING AND ANALYSIS OF MOLECULAR DYNAMICS OF SILICON-SOLVENT-VINPOCETIN SYSTEMS AND SILICON-SOLVENT-VINPOCETIN DIOXIDE - Yu. A. Polkovnikova; A. S. Lenshin; A. A. Glushko; O. M. Khishova (Разработка и регистрация лекарственных средств, 2019)
The process of desorption of vinpocetine on the surface of crystalline silicon and silicon oxide in various media has been studied by molecular dynamics modeling. The desorption of vinpocetine in water has been established both from the surface of silicon and from the surface of silicon oxide. The character of the desorption of vinpocetine from silicon and silicon oxide at pH 6.8 and pH 7 differs insignificantly (within the error of the simulation results). The desorption of vinpocetine in acidic medium (pH 2) from silicon and silicon oxide occurs more efficiently and at a higher rate, compared to pH 6.8 and pH 7.